Correlação de diferentes períodos de jejum com níveis séricos de cortisol, glicemia plasmática, estado clínico e equilíbrio ácido-base em case submetidos à anestesia geral inalatória - Guimarães, Simone Machado [UNESP]; Oliva, Valeria Nobre Leal de Souza [UNESP]; de Almeida Maia, Camila Aparecida [UNESP]; Del Rio Pinoti Ciarlini, Luciana [UNESP]; Perri, Silvia Helena Venturolli [UNESP]; da Silva, Alexandre Redson Soares [UNESP]; de Oliveira, Daniela Boaventura [UNESP]; Vivan, Maria Carolina Ribeiro [UNESP] (My University, 2007)
This study correlated the solid preoperative fasting periods with plasma glycemia, serum cortisol, condition clinic and acid-base balance in dogs submitted to inhalation of general anaesthesia. Eight adults, animals were distributed into three groups in accordance with solid preoperative fasting: group 1 (12 hours), group 2 (18 hours) and group 3 (24 hours). Gastric emptying was observed and following this animals were submitted to the same anesthetic procedure. Heart and respiratory rate, rectal temperature, capillary refill time, percent hydration and noninvasive arterial pressure determined before and after Acepromazine and every 10 minutes during anaesthesia, included ETCO 2; values blood gas (pH, PaCO 2, PaO 2, HCO 3, TCO 2, SaO 2, BE), glycemic and serum cortisol were analyzed before MPA and each 30 minutes during anaesthesia. In recovery anaesthetic, glycemia and serum cortisol were repeated. During anaesthesia there were little cardiovascular and respiratory alteration not having interference of the preoperative fasting periods. Animals with 12 hours of the preoperative fasting showed a higher rise in glycemia levels than others groups in recovery anaesthetic. Serum cortisol wasn't influenced by fasting. Solid preoperative fasting independent of the duration describe a discreet respiratory alkalosis. All animals showed good clinical condition in all three groups. Solid preoperative fasting of the 18 hours is recommended to ensure a complete absence of the solid food contents in stomach.
Correlation of the diferent fasting periods with serum cortisol, plasma glycemia, condition clinic and acid-base balance in dogs submitted to inhalation of general anaesthesia
Keywords: Acid-base balance; Cortisol; Dog; Fasting; Glycemia; Animalia; Canis familiaris